THE ISSUES OF THE DEFENCE AND SECURITY OF RUTHENIAN CITIES IN THE SEJMS OF THE POLISH-LITHUANIAN COMMONWEALTH IN THE 15TH – FIRST HALF OF THE 17TH CENTURY (City: History, Culture, Society, 2019)
The difficult international situation and the constant threat of war forced the king and nobility to pay special attention to the issues of state defence. The problem was often discussed at the Sejm sessions, including the question of the defence and order in the cities. Private and small towns, too, were not deprived of attention. Not only townspeople but also representatives of the nobility, first of all, starosta or vice-starosta were often made responsible for strengthening the defence capability of cities. The Sejms considered the building and strengthening of city walls, measures that would prevent their destruction, and providing cities with all necessary to counter hostile attacks. The Sejm constitutions not only exempted cities from some taxes so that the funds were used to strengthen the city walls but also protected them from the possible lawlessness of the nobility. The Sejms also prescribed the duties of the cities in the event of war and their involvement in the pospolite ruszenie. True, despite the difficult international situation, most of the Sejms’ resolutions were only addressed to individual cities. In practice, the issues of development and strengthening of cities did not rise in the Sejms systematically.
Keywords: city defence; city walls; munition; taxes; libertation; pospolite ruszenie; Sejm; Sejm constitution; border towns